Intracellular protein topogenesis - Blobel, Günter (1980)
Concurrently with or shortly after their synthesis on ribosomes, numerous specific proteins are unidirectionally translocated across or asymmetrically integrated into distinct cellular membranes. Thereafter, subpopulations of these proteins need to be sorted from each other and routed for export or targeted to other intracellular membranes or compartments. It is hypothesized here that the information for these processes, termed “protein topogenesis,” is encoded in discrete “topogenic” sequences that constitute a permanent or transient part of the polypeptide chain. The repertoire of distinct topogenic sequences is predicted to be relatively small because many different proteins would be topologically equivalent—i.e., targeted to the same intracellular address. The information content of topogenic sequences would be decoded and processed by distinct effectors. Four types of topogenic sequences could be distinguished: signal sequences, stop-transfer sequences, sorting sequences, and insertion sequences. Signal sequences initiate translocation of proteins across specific membranes. They would be decoded and processed by protein translocators that, by virtue of their signal sequence-specific domain and their unique location in distinct cellular membranes, effect unidirectional translocation of proteins across specific cellular membranes. Stop-transfer sequences interrupt the translocation process that was previously initiated by a signal sequence and, by excluding a distinct segment of the polypeptide chain from translocation, yield asymmetric integration of proteins into translocation-competent membranes. Sorting sequences would act as determinants for posttranslocational traffic of subpopulations of proteins, originating in translocation-competent donor membranes (and compartments) and going to translocation-incompetent receiver membranes (and compartments). Finally, insertion sequences initiate unilateral integration of proteins into the lipid bilayer without the mediation of a distinct protein effector. Examples are given for topogenic sequences, either alone or in combination, to provide the information for the location of proteins in any of the intracellular compartments or for the asymmetric orientation of proteins and their location in any of the cellular membranes. Proposals are made concerning the evolution of topogenic sequences and the relationship of protein topogenesis to the precellular evolution of membranes and compartments.